Pelatihan dan Penguatan Kompetensi Desain Materi Iklan Digital dengan Aplikasi Canva pada Siswa SMAN - Roslan, Astil Harli; Syahra, Syahra; Suparningsih, Suparningsih; Perkasa, Prayoga Oksa; Muharlisa, Nurfa; Salenda, Muliadin; Latifah, Nonik; Jatmiko, Budi; Nurasfidar, Nurasfidar (Pakis Journal Institute, 2025)
This community service activity aimed to improve the understanding and skills of students at SMA Negeri 2 Wangi-Wangi in designing digital advertising materials using the Canva application. Graphic design skills are increasingly relevant in today’s digital era, especially for the younger generation with the potential to become creative entrepreneurs. The training was carried out using an interactive approach, which included the delivery of theoretical design concepts, group discussions, and hands-on practice in creating advertising content through the Canva platform. The participants consisted of 30 students with an interest in digital content development. The results of this activity showed a significant improvement in participants' technical abilities in using Canva features, as well as their understanding of effective advertising design aesthetics. In addition, participants reported increased confidence in producing creative works that are ready to be used for digital promotional purposes. It can be concluded that training in the use of Canva is effective in enhancing students’ digital competencies in the Wangi-Wangi area. A recommendation for future activities is the need for continued mentoring to explore other creative platforms in order to further expand students’ digital literacy and capabilities.